Psychometric testing of the Indonesian version of the Resourcefulness Scale for older adults - Irna Kartina; Chieh-Yu Liu; Jaclene A. Zauszniewski; Chien Yu Lai (Belitung Nursing Journal, 2026)
Background: Resourcefulness is the capacity to confront life’s obstacles by utilizing coping skills, adapting to new circumstances, and seeking assistance from the environment. Therefore, the geriatric field continues to emphasize the importance of older adults’ resourcefulness. The Indonesian version of the Resourcefulness Scale© (I-RS) has just been translated; it is essential to conduct this research and report the findings for its application in Indonesia. Objective: This study intended to develop the Bahasa Indonesian version of the Resourcefulness Scale© and to test its reliability and validity in older adults. Methods: The questionnaire was initially created in English and then translated by two linguistic experts. Subsequently, meaning and cultural analysis were performed by psychiatric nursing specialists. Following this, a back-translation was executed, and the Indonesian version was used for data collection. Data was collected with 331 older adults residing in 11 nursing homes from 2023 to 2024. Correlational analysis and Confirmatory Factor Analysis (CFA) were conducted using Structural Equation Modeling (SEM) in LISREL 8.8 to examine the validity of the I-RS. Reliability was assessed using Cronbach’s Alpha and Split-half reliability. Results: The internal consistency of the Indonesian version of the instrument is acceptable with Cronbach’s Alpha .79 and Split-half reliability .75. According to the results of SEM, Chi square = 253.13, the Root means square error of approximation (RMSEA = 0.04), the adjusted goodness of fit index (AGFI = 0.90), Normed Fit Index (NFI = 0.92), Parsimony Normed Fit Index (PNFI = 0.76) and Comparative fit Index (CFI = 0.97) were all accepted.  Two factors, such as personal and social resourcefulness, were identified through factor analysis using SEM. A positive and significant relationship was found between resourcefulness and spiritual health (r = 0.45, p < 0.001). Conclusion: These results confirmed the use of the Indonesian version of the Resourcefulness scale (I-RS), indicating that it has acceptable reliability and validity. This instrument is potentially useful for measuring older adults’ resourcefulness in geriatric nursing in Indonesia, across both clinical and community settings.